Epidemiology of dermatophytosis in Northeastern Iran; A subtropical region - Maryam Ebrahimi (Current Medical Mycology, 2019)
Background and Purpose: Dermatophytes as the causative agents of dermatophytosis (ringworm) are widely spread around the world. Accurate identification of dermatophytes in one area can be particularly important for epidemiological studies. Regarding this, the aim of the present study was to describe the species spectrum of dermatophytes, isolated from patients in Mashhad city, Iran, using the molecular-based method. Materials and Methods: This study was conducted on 79 dermatophyte isolates obtained from the human skin, hair, and nail specimens. Species identification was performed by the polymerase chain reaction-restriction fragment length polymorphism analysis of ribosomal DNA internal transcribed spacer regions using MvaI restriction enzyme. Results: The identified species included Trichophyton mentagrophytes/T. interdigitale species complex (n=37, 46.8%), Epidermophyton floccosum (n=12, 15.2%), T. rubrum (n=8, 10.1%), Microsporum canis (n=8, 10.1%), T. violaceum (n=5, 6.3%), T. tonsurans (n=4, 5.1%), Nannizzia gypsea (n=3, 3.8%), T. benhamiae (n=1, 1.3%), and T. verrucosum (n=1, 1.3%). The clinical forms of infection were tinea corporis (n=26, 32.8%), tinea cruris (n=22, 27.8%), tinea capitis (n=10, 12.6%), tinea unguium (n=7, 9%), tinea manuum (n=6, 8%), tinea pedis (n=5, 6.3%), and tinea faciei (n=3, 3.5%). Conclusion: As the findings indicated, T. mentagrophytes/T. interdigitale species complex had the highest prevalence, and T. benhamiae appeared to be a new emerging agent of dermatophytosis in Mashhad, northeastern Iran.